HELIUM ABSOLUTE SPECTRA MEASUREMENT IN THE NUCLEAR INDUCED PLASMA - Kunakov, S.K. (Recent Contributions to Physics, 2018)
The experimental set and absolute spectra measurement are presented in the paper. Experimental results are presented and discussed. The methodological issues of the experiment are analyzed in details.